Market Efficiency and Related Theories: A Brief History - Weeraratne, S (NSBM Green University, 2018)
This paper mainly focuses on reviewing the theoretical phenomenon with regard to market efficiency. The paper lays the background for the analysis by elaborating the theory of Efficient Market Hypothesis; a theoretical phenomenon bought forward by E. Fama and explained under three different market forms; Weak form, Semi-strong form and Strong form. Each of the different form is elaborated with empirical findings, which both support and oppose the theory. Review it further extended to elucidate other related concepts such as Random walk theory and different Market Anomalies.
Keywords: —Efficient market hypothesis; Market Anomalies; Political Events